Phase shift formulas in uniaxial media: an application to waveplates - Veiras, Francisco Ezequiel (2010)
The calculation of phase shift and optical path difference in birefringent media is related to a wide range of applications and devices. We obtain an explicit formula for the phase shift introduced by an anisotropic uniaxial plane-parallel plate with arbitrary orientation of the optical axis when the incident wave has an arbitrary direction. This allows us to calculate the phase shift introduced by waveplates when considering oblique incidence as well as optical axis misalignments. The expressions were obtained by using Maxwell’s equations and boundary conditions without any approximation. They can be applied both to single plane wave and space-limited beams.